'Their interesting pictures made me buy it': exploring factors that influence Gen Y's buying intention on Instagram / Tengku Elena Tengku Mahamad and Lucia Rivadeneira - Tengku Mahamad, Tengku Elena; Rivadeneira, Lucia (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2021)
For more than a decade, social media platforms have been used as a tool for small and medium enterprises (SMEs) to market their products and services. However, many SMEs still believe in traditional marketing. With the recent age of the coronavirus (COVID-19) pandemic that have disrupted the global economy and restricted the physical movements of consumers, many sellers have quickly turned to social media such as Instagram due to poor sales. With thousands of businesses to compete with, small businesses are finding ways to market their products in an interesting and appealing way such as by posting attractive pictures and captions. This study aimed to explore the factors influencing Generation Y's (Gen Y) decision to purchase products sold on Instagram. Utilising a qualitative research method, this study gathered the perspectives of 15 Gen Y Instagram users living in the state of Selangor, Malaysia. Findings revealed that beautifully captured pictures can influence the purchase intentions of the users. Also, captions that describe the product well and with price can stop users from scrolling their Instagram timeline.